Спростіть вираз: 1) (2а + b)-(b - 2а); 3) (m + n) - (2m + n) - (m - 4n); 2) (3а - 4) +(3 - 5а); 4) (5с - 2) - (6с + 1) + (с - 8).

nkds00005 nkds00005    1   17.04.2019 01:10    3

Ответы
Мини196 Мини196  17.04.2019 01:10
Відповідь:

1) (2а + b)-(b - 2а) = 2a + b - b + 2a = 4a;
2) (3а - 4) +(3 - 5а) = 3a - 4 + 3 - 5a = -2a - 1;
3) (m + n) - (2m + n) - (m - 4n) = m + n - 2m - n - m + 4n = -2m + 4n;
4) (5с - 2) - (6с + 1) + (с - 8) = 5c - 2 - 6c - 1 + c - 8 = -11.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Другие предметы